The Physician Scientist's Career Guide - Eisenberg, Mark J.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
The Physician Scientist$1 (Bs Career Guide provides a complete guide to having a successful career as a Physician Scientist. Filled with first-hand experiences and practical advice, it guides readers through each step of this career path, from choosing a degree and training program, to navigating the tenure track, and through the intricacies of applying for and obtaining funding. The volume is unique in that it provides an overview of this entire career path, allowing readers to envision and prepare for their futures. The Physician Scientist$1 (Bs Career Guide fulfills a unique and crucial need and is an invaluable guide for medical students, fellows and newly appointed faculty members interested in a career in research.s
Keywords: Medicine; Internal medicine; Surgery; Medicine & Public Health; Medicine/Public Health, general; Internal Medicine; General Surgery